Efficacy of In-office Bleaching Gel One Week After Mixing: A Randomized Clinical Trial. - de Freitas, IM; Carneiro, TS; Forville, H; Favoreto, MW; Wendlinger, M; Ñaupari-Villasante, R; Gonçalves, SEP [UNESP]; Vallejo-Izquierdo, L; Loguercio, AD (Operative Dentistry, 2025)
Objective: This randomized clinical trial aimed to evaluate the efficacy, risk and intensity of tooth sensitivity (TS) and gingival irritation (GI), and esthetic self-perception of in-office dental bleaching using a bleaching gel 1 week after mixing. Methods and Materials: Forty subjects underwent in-office bleaching with 40% hydrogen peroxide (Opalescence Boost PF, Ultradent). In a splitmouth design, each maxillary hemiarch received bleaching gel that was mixed during, or 1 week before, the treatment session. The bleaching procedure was performed in two sessions of 40 minutes with a 7-day interval. Tooth color was assessed before treatment, and 1 week, 2 weeks, and 1 month after the end of bleaching, using a digital spectrophotometer (Vita Easyshade; ΔEab, ΔE00, and ΔWID) and subjective scales (Vita Classical and Vita Bleachedguide; ΔSGU). The risk and intensity of TS and GI were recorded using a Visual Analogue Scale (0-10). Esthetic self-perception was assessed using the Orofacial Esthetic Scale (0-10). Results: Satisfactory bleaching was achieved in both groups, with no significant differences for objective (ΔEab, ΔE00, and ΔWID; p>0.72) or subjective (ΔSGU [shade guide units], p>0.84) color assessments. No significant differences were found in the risk and intensity of TS (p=0.79; p=0.67) or GI (p=1.0; p=0.85). Patients' esthetic self-perceptions changed after the procedure (p<0.009), mainly on the tooth color question (p<0.001). Conclusion: In-office dental bleaching with Opalescence Boost PF 40% remained effective, without differences in risk and intensity of TS and GI, even 1 week after mixing.